Long-term Protoplanetary Disk Evolution from Molecular Cloud Core Collapse and Implications for Planet Formation. II. Strong Disk Self-gravity - Xin-Ming Wang (The Astrophysical Journal, 2023)
We continue to investigate long-term protoplanetary disk evolution and focus on the situation of strong disk self-gravity (DSG). We call such a disk a type III disk. A large amount of mass is stored in the disk due to large angular momentum. When the disk becomes massive enough, a dense region (DR) is formed due to gravitational instability. This instability is triggered by the combined effect of radial gravitational attraction and a decrease in disk scale height. Viscosity cannot smooth out the DR due to strong DSG. We further investigate the subsequent disk evolution under the assumption of axisymmetry. Besides the viscous process, angular momentum flux caused by the perturbation of DSG also plays a role in the transport of angular momentum. The combination of the two processes results in the efficient transport of angular momentum in the outer disk and prevents the disk from becoming very massive. Due to the interaction between the DR and the inner disk, a gap between them is formed. This gives a nonplanetary origin of the gap. In ∼10 ^6 yr, a surface density plateau and a very low surface density region are formed in the inner disk. In a type III disk, there are several locations where the radial drift of solids can be stopped. Objects formed in the DR may remember some of the properties of the DR, such as large mass and large angular momentum. In particular, a planetary system with wide-orbit giant planets may be formed in the DR. Finally, it is still difficult to identify what type of disk the solar nebula belongs to.